Factors affecting long‐term changes of liver stiffness in direct‐acting anti‐hepatitis C virus therapy: A multicentre prospective study. Issue 1 (13th October 2021) - Rosato, Valerio; Ascione, Antonio; Nevola, Riccardo; Fracanzani, Anna Ludovica; Piai, Guido; Messina, Vincenzo; Claar, Ernesto; Coppola, Carmine; Fontanella, Luca; Lombardi, Rosa; Staiano, Laura; Valente, Giovanna; et al.
Abstract: The long‐term changes of liver stiffness (LS) in patients who achieve viral clearance after direct‐acting anti‐HCV therapy remain undefined. We conducted a multicentre prospective study to investigate this aspect. Patients with HCV infection treated with DAAs were enrolled from six Italian centres; they underwent clinical, biochemical, ultrasound and transient elastography evaluations before treatment (T0), 12 weeks (SVR12) and 24 months (T24) after the end of therapy. Among the 516 consecutive patients enrolled, 301 had cirrhosis. LS significantly decreased from T0 to SVR (14.3 vs 11.1 kPa, p  = .002), with a progressive reduction until T24 (8.7 kPa, p  < .001). However, only patients with steatosis and those who developed HCC did not experience a late improvement in LS. Multivariate analysis of baseline and follow‐up variables identified steatosis as the only independent predictor of failure of LS improvement (OR 1.802, p  = .013). ROC curve analysis of the association of LS with the risk of developing HCC showed that SVR12 ≥14.0 kPa had the highest accuracy (sensitivity 82%, specificity 99%; AUC: 0.774). Multivariate analysis revealed that LS was the only variable independently associated with an increased risk of developing HCC (OR 6.470, p  = .035). Achieving an SVR was associated with a progressive, long‐term decline of LS, suggesting a late improvement in liver fibrosis, besides the resolution of inflammation. Fatty liver and the development of HCC interfered with late reduction of LS. Patients with an LS ≥14 kPa at 12 weeks after the end of treatment were at higher risk for developing HCC.